Conceptualizing Islamophobia and The Identification of American Muslims’ Reaction in the 21st Century Case Study: Contact Theory - BRAHIMI, Ahmed Taha; ADJEB, Mohamed Abdel Ellah; Guellil, Assia (Faculty of Letters and Foreign Languages Department of English, 2023)
This study aims to identify both Islamophobia in the 21st century and the Muslims’ reaction as a form of a social movement under the name of Dismantling and Countering Islamophobia, followed by a suggested case study that will expound on the phenomenon. Islamophobia is a religion-based racism that affects millions of lives and threatened the national security of multi-racial Western civilizations with the increasing levels of the phenomenon in the modern world. However, Islamophobia is a liquid term and a shape shifting phenomenon through periods and in various forms. This study approaches the problem of misunderstanding and the conflicts between Islamophobic individuals and Muslims, through theory study -Theory of Contact- and secondary data analysis provided by various scholars to manage a potential success to reduce levels of prejudice and discrimination among Westerners and Muslims followed by its hypothesis to be demonstrated on both groups. The movement of Dismantling and Countering Islamophobia wasn't that successful. Therefore, the application of Contact Theory is highly needed to achieve higher results in the process of reducing prejudice and tension. This study aims to provide a better and deeper understanding of the phenomenon and an efficient tool to encounter it. Further progressive studies are needed to enhance and develop more effective methods to encounter the phenomenon properly.